Keudah and Peunayong: Traces of melting pot architecture, interior and landscape in Banda Aceh (ARTEKS : Jurnal Teknik Arsitektur, 2025)
According to research findings from a national private institute, Banda Aceh was labelled an intolerant city in 2023 and 2024. The information contrasts the history of Banda Aceh as a cosmopolitan city, featuring numerous architectural artefacts and lesser-known cross-cultural landscapes. This study aims to document the history and current architectural, interior, and landscape conditions of two melting pot settlements in Banda Aceh: Gampong Keudah, also known as the Indian Enclave, and Gampong Peunayong, also referred to as the Chinese Enclave. Historical research, visual archives, and socio-cultural examinations can enrich the conceptualisation and design proposals for the area, thereby facilitating the development of regional spatial plans and improving the tolerance index moving forward. This research employs a historical research methodology that encompasses four primary components: a literature review of historical writings and scholarly articles; an examination of artefacts, including sixteenth- to nineteenth-century maps and Dutch colonial photographs; photographic documentation and architectural surveys of the historic urban landscape (HUL); and the collection of oral histories through interviews. The historical research methodology documented various typologies, including temple exteriors and interiors, marketplace structures, traditional shophouses, and multiethnic cemetery landscapes. These findings demonstrate the persistence of cross-cultural architectural traditions that challenge contemporary perceptions of Banda Aceh's tolerance levels.
Keywords: Architectural history of Aceh; Cross-cultural; Historical research; Melting pot; Tolerance